Abscisic acid dynamics, signaling, and functions in plants. Issue 1 (21st January 2020) - Chen, Kong; Li, Guo‐Jun; Bressan, Ray A.; Song, Chun‐Peng; Zhu, Jian‐Kang; Zhao, Yang
Abstract : Abscisic acid (ABA) is the major stress hormone that coordinates plant growth, development and abiotic stress responses. In this review, we summarized the recent progresses on its metabolism, transport and signaling, and discussed the open questions about ABA dynamics and functions. Abstract: Abscisic acid (ABA) is an important phytohormone regulating plant growth, development, and stress responses. It has an essential role in multiple physiological processes of plants, such as stomatal closure, cuticular wax accumulation, leaf senescence, bud dormancy, seed germination, osmotic regulation, and growth inhibition among many others. Abscisic acid controls downstream responses to abiotic and biotic environmental changes through both transcriptional and posttranscriptional mechanisms. During the past 20 years, ABA biosynthesis and many of its signaling pathways have been well characterized. Here we review the dynamics of ABA metabolic pools and signaling that affects many of its physiological functions.